Diagnosis of paroxysmal supraventricular arrhythmia (PSVT) in a professional cyclist: the utility of performance monitoring tools as a medical support - Bidoglio, F.; Poerio, C. S.; Testa, M.; Bottinelli, R.; Zaccaria, D. (Medicina dello Sport, 2021)
Athletes who complain of cardiac like symptoms represent a diagnostic challenge for sports medicine and cardiologists. Underlying electro-cardiac anomalies may be misunderstood by common cardiological evaluation tests at the beginning of the sporting season. The possibility of using dedicated devices to monitor biometric parameters during performance would provide real support in diagnosing arrhythmic events caused by repeated and intense workloads typical of the sport practiced. The diagnostic-therapeutic approach reserved for such patients ought to take into account the clinical picture, information obtained from investigations carried out and the presence of predisposing conditions. We report the clinical picture of an elite athlete with symptomatology attributable to rhythmic disorders in order to underline the difficulty and importance of biometric monitoring of performance.